Blood pressure variability and cardiovascular disease: A systematic review and meta-analysis - Stevens, S; McManus, R; Stevens, R; Koshiaris, C; Wood, S; Glasziou, P; Law, K (BMJ Publishing Group, 2016)
Objective Variability in blood pressure (BP) has been increasingly recognized as an independent risk factor for cardiovascular disease (CVD) over and above mean BP. Conflicting results from previous studies reflect heterogeneity of approach and failure to consider confounders. We systematically reviewed studies quantifying the associations of long (clinic), mid- (home) and short term (ambulatory) BP variability, independent of mean BP, with CVD events and mortality. Data Sources Medline, Embase, Cinahl and Web of Science were searched to 15th February 2016 for full text articles in English. Eligibility Criteria for Selecting Studies Prospective cohort studies or clinical trials in adults were included, except those in haemodialysis patients, where the condition may directly impact BP variability. Standardized hazard ratios were extracted and, if there was little risk of confounding, combined using random effects meta-analysis in main analyses. Outcomes included all-cause and CVD mortality and CVD events. Measures of variability included standard deviation, coefficient of variation, variation independent of mean and average real variability but not night dipping or day-night variation. Results Forty-one papers representing nineteen observational cohort studies and seventeen clinical trial cohorts, and forty-six separate analyses were identified. Clinic, home and ambulatory BP variability was studied in twenty-four, four and fifteen papers respectively (two studied both clinic and ambulatory variability). Results from twenty-three analyses were excluded from main analyses due to high risks of confounding. Increased long-term variability in clinic systolic BP was associated with risk of all-cause mortality (HR=1.15, 95% CI [1.09 to 1.22]), CVD mortality (HR=1.18, 95% CI [1.09 to 1.28]), CVD events (HR=1.18, 95% CI [1.07 to 1.30]), coronary heart disease (HR=1.10, 95% CI [1.04 to 1.16]) and stroke (HR=1.15, 95% CI [1.04 to 1.27]). Increased mid-term (home) systolic BP variability and short-term daytime systolic BP variability were also associated with all-cause mortality (HR=1.15, 95% CI [1.06 to 1.26] and HR=1.10 95% CI [1.04 to 1.16]). Conclusions Long-term clinic BP variability is associated with cardiovascular and mortality outcomes, over and above the effect of mean BP. Associations are similar in magnitude to those of cholesterol measures with CVD. Limited data for home/ ambulatory variability showed similar associations. Future work should focus on the clinical implications of BP variability assessment and avoid the common confounding pitfalls observed to date.